Magnetoresistance in magnetic tunnel junctions with amorphous electrodes - FENG, GEN; COEY, JOHN MICHAEL DAVID (IEEE, 2005)
Magnetic tunnel junctions (MTJs) with amorphous CoFeB and Co2MnSi electrodes were fabricated and examined. In the case of [Co90Fe10]100 B , the = 32%boron addition reduces the magnetization by 30% compared to Co90Fe10, yet the reduction of the tunnel magnetoresistance (TMR) is over 95%. On the contrary, in the case of Co(100 )Mn Si , although net magnetization is very small at room temperature, the TMR can be as large as 7%. The character of each metalloid (boron and silicon) could be responsible for the peculiar behavior to each system.
PUBLISHED
Keywords: Amorphous, MTJ, spin-dependent tunneling.